Construction of an Immune-Related Six-lncRNA Signature to Predict the Outcomes, Immune Cell Infiltration, and Immunotherapy Response in Patients With Hepatocellular Carcinoma - Zhou, Pengcheng; Lu, Yuhua; Zhang, Yewei; Wang, Lei (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is one of the most lethal malignant tumors worldwide and has poor prognosis. Growing evidence have demonstrated that long non-coding RNAs (lncRNAs) and immune-related gene can serve as biomarkers for cancer diagnosis. This study aimed to identify an immune-related lncRNA signature in HCC for the prospective assessment of prognosis. HCC RNA-seq data and clinical information were downloaded from the The Cancer Genome Atlas (TCGA) project database. We used ESTIMATE to evaluate the tumor microenvironment (TME) and CIBERSORT to estimate the abundance of tumor-inﬁltrating immune cells. Using Cox regression model and survival analysis, we identified a six immune-related lncRNAs (MSC-AS1, AC145207.5, SNHG3, AL365203.2, AL031985.3, NRAV) with the ability to stratify patients into high- and low-risk groups with significantly different survival. Univariate Cox regression, multivariate Cox regression, ROC and stratification analyses conﬁrmed that the six immune-related lncRNA signature was a novel independent prognostic factor in HCC patients. Functional analysis suggested that the six immune-related lncRNA signature may be involved in the immune-related biological processes and pathways. Furthermore, CIBERSORT method showed that the six immune-related lncRNA signature was associated with the infiltration of immune cells in HCC. Finally, a quantitative real-time polymerase chain reaction assay demonstrated that the six lncRNAs were signiﬁcantly differentially expressed in HCC cell lines and normal hepatic cell line. In summary, our study demonstrated that this signature has important clinical implications for improving predictive outcomes in HCC patients and could be potential molecular markers affecting the outcome of HCC patients.